Studi Minat Beli Kembali Lipstik Hanasui: Peran Brand Image dan Kelompok Referensi - Hendri, Novi; Meidona, Syofria; Wahyuni EDT, Risa (Jurnal Point Equilibrium Manajemen dan Akuntansi, 2025)
This study aims to determine the influence of brand image and reference groups on repurchase intention of Hanasui lipstick cosmetic products among university students in Pariaman City, using a sample of 75 respondents. The background of this research stems from the increasing number of business players in the cosmetics industry, which has intensified market competition. Preliminary surveys indicate that the brand image of Hanasui lipstick is still not optimal and has not succeeded in making the brand a market leader or widely recognized by consumers. This research adopts a quantitative approach with a cross-sectional study design. Primary data were collected through questionnaires that were tested for validity and reliability. The data analysis techniques used include multiple linear regression, classical assumption tests, hypothesis testing (t-test and F-test), and coefficient of determination analysis. Data processing was conducted using SPSS version 27. The results show that the t-count value for the brand image variable (X1) is 5.044 with a significance of 0.000 (< 0.05), indicating a significant effect on repurchase intention. The reference group variable (X2) has a t-count of 2.381 with a significance of 0.019 (< 0.05), also showing a significant effect. Simultaneously, the F-count value is 23.400 with a significance of 0.000 (< 0.05), which means both variables significantly influence repurchase intention. The coefficient of determination (R²) is 0.606, indicating that 60.6% of the variation in repurchase intention is influenced by brand image and reference groups, while the remaining 39.4% is influenced by other variables not examined in this study.